Rural Community Income from Rubber Farmers to Gold Miners in Nagari Padang Laweh, Koto VII Sijunjung District - Irwan, Irwan; Oktarin, Erin Sonia (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Rural communities experienced a change in livelihood from rubber to gold mining. This results in disruption of income for the community. The focus of this research is to analyze the income of rural communities from rubber farmers to gold miners in Sijunjung. This research uses White's theory about livelihoods. This research uses a qualitative approach with descriptive research type. The data collection method begins with participant observation, in-depth interviews and document study. Data analysis uses Milles Hubermen, starting with data collection, data reduction and data presentation. The results of this research show that changes in livelihoods have an impact on the livelihoods of rural communities. These changes can be seen in economic life and lifestyle. In addition, the changes show an accumulation of additional gold mining vessels.